Pelatihan Penentuan Harga Jual UMKM Pabrik Tahu Tempe di Kabupaten Boalemo - Heldy Vanni Alam; Valentina Monoarfa; Zihan Putri Maharani Montu; Nurara Rahim; Muthiah Syahidah (Komunal Jurnal Pengabdian Masyarakat, 2022)
Selling price is the monetary amount charged by a business unit to buyers or customers for goods or services sold or delivered. The purpose of the selling price determination method compiled and presented by several tofu and tempeh factories in Gorontalo is to provide information on how to determine product selling price by using the concept of total cost, product cost concept and variable cost concept. The research method that the author uses is a descriptive approach. The results show that some Tofu and Tempe factories already understand determining the selling price of the product. However, the problem is with UMKM in the Tofu and Tempe Factory in Gorontalo and UMKM in Kab. Boalemo still uses a simple method. For this reason, we, the authors, seek this service activity so that the UMKM of the Tofu and Tempe Factory in Gorontalo and the UMKM in the District. Boalemo is able to determine the selling price of the product by using the concept of total cost, product cost concept and variable cost concept.